Describing Human–Wildlife Interaction from a European Perspective. Issue 2 (3rd March 2016) - Johansson, Maria; Dressel, Sabrina; Kvastegård, Emma; Ericsson, Göran; Fischer, Anke; Kaltenborn, Bjørn P.; Vaske, Jerry J.; Sandström, Camilla
ABSTRACT: European researchers from both the natural and social sciences show growing interest in studying interactions between society and wildlife. A wealth of theoretical frameworks, concepts, and methods are used, but an integration of perspectives is lacking. This research note summarizes results from two workshops that included 63 delegates from 25 European countries, as well as a follow-up survey of 41 respondents. Two main theoretical approaches to the study of human–wildlife interactions were identified. One approach focuses on the collective societal level relying on theories of governance, social representation, deliberative procedures, and commons theory. The other approach targets individuals or groups, and is based on theories such as the cognitive hierarchy, theory of reasoned action, and theory of planned behavior. Interdisciplinary collaboration is needed to identify the best options for wildlife conservation and management in a more politically integrated Europe.